La «gestión de la diversidad» a través del patrimonio cultural. Entre la reificación de «la comunidad» y la reflexividad cultural - López López, Juan de Dios (Comparative Cultural Studies: European and Latin American Perspectives, 2018)
The main aim of this article is to analyze the heritage processes, carried out by cultural institutions, as an instrument for the «management of diversity». In this way and indirectly, it is intended to show a possible way to take the reflection on cultural diversity and other associated phenomena, such as interculturality or multiculturalism, beyond migrant subjects or ethnicized and racialized groups, over whom the research on diversity are usually revolved around. The text begins by explaining the link between heritage policies and the “management of diversity”, and the notion of culture behind this link. Next, I consider the role of cultural heritage in the definition and conformation of certain collective subjects. And, finally, heritage processes are shown as privileged contexts for cultural reflexivity and the possibilities of involvement of critical social sciences in these processes are examined.